2010
DOI: 10.7861/clinmedicine.10-5-464
|View full text |Cite
|
Sign up to set email alerts
|

A structured course teaching junior doctors invasive medical procedures results in sustained improvements in self-reported confidence

Abstract: -Pressure on working hours has led to a decrease in opportunities for training in invasive medical procedures for junior doctors. The effect of a structured course on immediate and medium-term changes in selfreported confidence was investigated. A one-day modelbased practical course was run on two separate occasions teaching central venous line placement, lumbar puncture, Seldinger-technique chest drain insertion and knee joint aspiration. Attendees were asked to indicate their confidence in each procedure on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 17 publications
0
10
0
1
Order By: Relevance
“…Further studies are needed to investigate these effects in real life. Although we could not test for the long‐term retention of our results, related studies have demonstrated a perpetuation of initially set standards for bedside procedures, both in general (Garrood et al, ), and for LP (Tung, ).…”
Section: Discussionmentioning
confidence: 78%
“…Further studies are needed to investigate these effects in real life. Although we could not test for the long‐term retention of our results, related studies have demonstrated a perpetuation of initially set standards for bedside procedures, both in general (Garrood et al, ), and for LP (Tung, ).…”
Section: Discussionmentioning
confidence: 78%
“…Hence there is a requirement for developing structured training activities and assessment methods to replace the traditional chair side training. The medical literature review also supported our concept that structured methods aiming to teach novice have led to sustained improvements in self-reported confidence [4,5]. …”
Section: Introductionmentioning
confidence: 82%
“…Nesse manequim o cateter deve ser curto devido o comprimento do balão. É importante ressaltar que mesmo diante dessas intempéries, o modelo demonstra por completo toda a técnica de dissecção venosa da veia basílica, podendo ser expandidas para outros sítios de dissecção, apenas mudando as referências anatômicas [13][14][15] .…”
Section: Discussionunclassified